Studying the efficacy of the plant extract of Tetracera scandens as an antidiabetic treatment - Thallaj, Nasser; alallan, Louai; Khazem, Mays (Latakia University Journal -Medical Sciences Series, 2023)
In Indonesia, a metabolic disease with a high prevalence was known as diabetes mellitus.Diabetes mellitus was treated with traditional medicinal plants.Tetracera scandens (L.) Merr is one of them.The purpose of this study was to assess the homeostatic model of insulin resistance (HOMA-IR) and blood glucose levels in alloxan-induced mice in order to determine the ethanol extract of T.scandens strains' anti-diabetic activity.There were five groups of animals:normal group, a negative control, and extract dosages of 175, 350, and 700 mg/kg body weight, respectively.The animals were given 175 mg/kg body weight of alloxan to induce their behavior.The extract was taken orally for 21 days.Ethanol extract from T.scandens strains was found to significantly lower blood glucose levels, increase insulin levels, and reduce insulin resistance when administered (p 0.05).As a result, it is possible to draw the conclusion that the ethanol extract of T. scandens could be used to treat diabetes mellitus.